1976
DOI: 10.1002/eji.1830061002
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity in the clonal repertoire for the immune response to phosphorylcholine in mice

Abstract: A comparison of the clonal nature of the immune response to phosphorylcholine (PC) was made in nine different inbred mouse strains. Quantitative idiotypic analysis showed that anti-PC antibodies from each strain were composed of antibodies bearing binding-site idiotypic determinants indistinguishable from two different BALB/c myeloma proteins, T15 and M511. Idiotypic determinants of two other PC-binding proteins, M167 and M603, were not detected. Isoelectric focusing of the light (L) chains verified the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…This serum has been shown to lack protective antibodies to phosphocholine (7). Non-CBA/N mouse serum contains natural antibodies reactive with teichoic acids (12,13). These antibodies, especially those of the IgG isotypes can be protective (4,5).…”
Section: Analysis Of Complement Deposition On Pspamentioning
confidence: 99%
“…This serum has been shown to lack protective antibodies to phosphocholine (7). Non-CBA/N mouse serum contains natural antibodies reactive with teichoic acids (12,13). These antibodies, especially those of the IgG isotypes can be protective (4,5).…”
Section: Analysis Of Complement Deposition On Pspamentioning
confidence: 99%
“…In the response to phosphorylcholine (PCho) of the BALB/c mouse which is characterized by dominance of the HOPC-8 (H8) idiotype (9)(10)(11)(12)(13), it has been shown that liver, spleen, and bone marrow of the neonate do not contain PCho-specific precursor cells. At age 1 week, the H8 clone appears in the spleen and bone marrow (14).…”
mentioning
confidence: 99%
“…The immune response to phosphocholine involves at least three different types of K light chains represented by the myelomas TEPC15, M603, and M511/M167 (21,22 Somatic diversification mechanisms had previously been proposed in the A light chain immunoglobulin system from a comparison of DNA molecular hybridization data with the amino acid sequences of several myeloma proteins (23,24). In short, several proteins appear to be derived from only a few (or one) VA genes (25,26) What somatic mechanisms could explain the generation of the M511 or M167 sequence and these other somatic variants from the single-copy prototype VK24 germ-line gene?…”
Section: Discussionmentioning
confidence: 99%